2008
DOI: 10.1002/jnr.21956
|View full text |Cite
|
Sign up to set email alerts
|

High glucose changes extracellular adenosine triphosphate levels in rat retinal cultures

Abstract: Diabetic retinopathy (DR) is the leading cause of blindness in adults. In diabetes, there is activation of microglial cells and a concomitant release of inflammatory mediators. However, it remains unclear how diabetes triggers an inflammatory response in the retina. Activation of P2 purinergic receptors by adenosine triphosphate (ATP) may contribute to the inflammatory response in the retina, insofar as it has been shown to be associated with microglial activation and cytokine release. In this work, we evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 31 publications
5
29
0
Order By: Relevance
“…Thus, it has been shown that ATP stimulates intracellular calcium activity in perivascular cells [34,35], and intracellular calcium levels are elevated in retinal cell cultures exposed to hyperglycaemia [8]. Furthermore, retinal blood flow is affected by activation of P 2 receptors in alloxan-induced diabetes in rabbits [36,37], and a recent study has shown that ATP relaxation of porcine retinal arterioles exposed to hypercholesterolaemia in vivo is modified by both hepatic low-density lipoprotein receptor deficiency and diabetes mellitus [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been shown that ATP stimulates intracellular calcium activity in perivascular cells [34,35], and intracellular calcium levels are elevated in retinal cell cultures exposed to hyperglycaemia [8]. Furthermore, retinal blood flow is affected by activation of P 2 receptors in alloxan-induced diabetes in rabbits [36,37], and a recent study has shown that ATP relaxation of porcine retinal arterioles exposed to hypercholesterolaemia in vivo is modified by both hepatic low-density lipoprotein receptor deficiency and diabetes mellitus [38].…”
Section: Discussionmentioning
confidence: 99%
“…The purine adenosine triphosphate (ATP) is a carrier of energy in the intermediary metabolism [2] but has also been shown to act as an extracellular signalling molecule [3] and to participate in the regulation of retinal vascular tone by stimulation of purine P 2 receptors [4,5,6]. ATP metabolism is known to be disturbed, and concentrations are increased in the vitreous body in diabetic patients [7,8,9,10], which supports that ATP may be involved in the pathophysiology of diabetic retinopathy. The vaso-active effects of ATP may depend on ATP-induced ATP release, as shown in cardiac vessels [11,12], or be mediated by purinergic receptors [13] stimulated by degradation products of ATP [6] or through the release of other vaso-active compounds such as cyclo-oxygenase (COX) products [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…ATP can also be released from pigmented epithelium (PE) by the opening of connexin 43 hemmichanels [13] or NMDA receptor stimulation [14]. Recently, the release of ATP in the retina or in cultures of retinal cells was observed in pathological conditions such as high glucose [15] or elevated intraocular pressure [16].…”
Section: Introductionmentioning
confidence: 99%
“…High glucose conditions increase secretion and reduce degradation of extracellular ATP in retinal cell culture [3], with increased purine concentrations being reported in the vitreous of diabetic patients suffering from proliferative retinopathy [4]. Administration of simvastatin, a lipophilic HMG-CoA reductase inhibitor, did not only promote direct vasculoprotective effects in experimental in vitro and ex vivo models [5], but was also associated with low levels of vasoactive and tissue remodelling factors in the retinas of diabetic rats [6] and vitreous of diabetic patients [7].…”
mentioning
confidence: 99%